Expanding the Ethnographic World of Young People in Aesthetic Culture - Tagaev Ganisher Hasanovich (International Journal on Integrated Education, 2021)
This article discusses the reflection of the expansion of the ethnographic worldview of young people in the aesthetic culture, as well as the influence of geographical, religious and historical criteria. The stages of formation and development of ethnocultural processes in the territory of Uzbekistan are analyzed from the point of view and essence of the period. Among the alien influences that affect the mentality, the factors that contribute to the formation of ethnoculture, namely the influence of society, the chain of cultural relations, the attitude of people to them, are also widely revealed.